PENGARUH PEMAHAMAN AKUNTANSI, PEMANFAATAN SISTEM INFORMASI AKUNTANSI, DAN PERAN INTERNAL AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PLN UPT MALANG - Mochamad Rizki Dwi Saputra; Abdul Wahid Mahsuni; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to determine and analyze the effect of understanding accounting, utilization of accounting information systems, and the role of internal audit on the quality of the financial statements of PLN UPT Malang. The population of this research is all employees of PLN UPT Malang who work in the field of financial administration. While the sample is 42 employees who work in the administration and finance of PLN UPT Malang which was taken using purposive sampling. This data was obtained from the PLN UPT Malang office. The data of this study were analyzed by multiple linear regression method. The results of this study indicate that (1) accounting understanding affects the quality of the financial statements of PLN UPT Malang, (2) the use of accounting information systems affects the quality of the financial statements of PLN UPT Malang, (3) the role of internal audit affects the quality of the financial statements of PLN UPT Malang.Keywords: Accounting Understanding, Utilization of Accounting Information Systems, Role of Internal Audit, Quality of Financial Reports